Morphological characteristics and phylogenetic analyses revealed two additional taxa in Cyathus (Agaricales, Basidiomycota) - Duan, Zi-Yan; Yang, Xin; Liu, Chao-Mao; Zhao, Chang-Lin (Phytotaxa, 2023)
Two new species of the bird’s nest fungus, Cyathus asiaticus and C. prismaticus are proposed based on a combination of the morphological and molecular evidence. Cyathus asiaticus is characterized by having an obconical, campanulate to cupulate basidiomata with the inconspicuously striation on the inner surface of the peridium, smooth mouth, silver gray to black peridioles with funicular cord, a monomitic hyphal system bearing the generative hyphae with clamp connections and broadly ellipsoid, elliptical, subglobose, ovoid, irregular, thick-walled basidiospores with inconspicuous apiculus. Cyathus prismaticus is characterised by the infundibuliform, obconical to cupulate basidiomata covered with shaggy or hirsute hairs, presence of the striations on the outer and inner surface of the peridium, peridioles with the funicular, a dimitic hyphal system with generative hyphae having clamp connections, prensence of the narrow oblique prisms and subglobose, ovoid, elliptical to broadly ellipsoid, thick-walled basidiospores. Sequences of ITS and nLSU rRNA markers of the studied samples were generated, and the phylogenetic analysis were performed with maximum likelihood, maximum parsimony and Bayesian inference methods on two datasets (ITS+nLSU and ITS). The dataset analysis showed that two new species clustered into the genus Cyathus.